Molecular Characterization of Multidrug-resistant Bacteria Isolated From Patients With Pneumonia at Two Hospitals in North-West Nigeria - Paul Oyegoke; Busayo Olayinka; Joseph Ehinmidu; Babajide Tytler (Shahrekord University of Medical Sciences, 2021)
Background and aims: The spread of antimicrobial resistance (AMR) is a serious public health threat complicating treatment and resulting in prolonged hospitalization. The prevalence of AMR threat is not well defined due to the dearth of appropriate surveillance systems. This study sought to assess the prevalence of AMR among bacterial isolates from sputum specimens obtained from patients with pneumonia presenting at two secondary healthcare facilities in Zaria from June 1 to August 31, 2018.   Methods: Standard methodology was followed in processing sputum samples that met the acceptance criteria. The antibiotic susceptibility patterns of bacterial pathogens cultured from sputum specimens obtained from June 1 to August 31, 2018) were evaluated using the recommendation of the Clinical and Laboratory Standards Institute. Finally, data were analyzed using descriptive statistics.   Results: Acinetobacter spp. were the predominant pathogens accounting for 32% of recovered isolates, followed by Staphylococcus spp. (18%) and Klebsiella spp. (17%), respectively. AMR was found in 91% of the isolates. Most isolates were resistant to erythromycin (ERY) (80%) and amoxicillin (83.3%). Eventually, the multiple antibiotic resistance index ≥0.3 was observed in 76% of the isolates.   Conclusion: Based on the findings, AMR rates were observed to be high, and may display a serious therapeutic challenge to the management of community-acquired pneumonia. Concerted efforts are needed to combat the worrisome AMR trends revealed in this study.